Pengaruh Implementasi Penanaman Nilai Toleransi Dalam Pendidikan Karakter Melalui Kegiatan Ekstrakulikuler Pramuka di SD Negeri Babalan Lor 2 - Syafira, Alfina; Nurharini, Atip; Qamarudin, Ali; Utami, Arinta Widya Kasi; Khoirunisa, Nur Salsa (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Character education is an important aspect in developing individuals with integrity and good personality. One of the essential character values is the value of tolerance, which plays a key role in building harmonious relationships in a multicultural society. Elementary school has an important role in shaping children's character because it is the initial stage in their learning process. Extracurricular activities, such as Scout activities, are considered an effective means of instilling character values in a formal education environment. This research aims to explore the influence of the implementation of instilling the value of tolerance through Scout extracurricular activities on the character education of students in elementary schools. The main focus is to understand how Scout activities can play a role in strengthening the value of tolerance among students. It is hoped that the results of this research will provide deeper insight into the role of extracurricular activities in shaping student character, especially in terms of developing attitudes of tolerance towards differences.